2001
DOI: 10.1542/peds.107.3.e35
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Adjustment of Adolescent Girls With Chronic Fatigue Syndrome

Abstract: ABSTRACT. Objective. To examine psychosocial problems and adaptation of adolescent girls with chronic fatigue syndrome (CFS).Methodology. Thirty-six adolescent girls with CFS (mean age: 15.2 years; mean syndrome duration: 19.7 months) who fulfilled the criteria of the Centers for Disease Control and Prevention were examined by interviews regarding premorbid problems and by questionnaires regarding psychosocial functioning and distress, psychological attitudes, and coping resources. Data were compared with norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 27 publications
3
25
0
Order By: Relevance
“…Our study is consistent with previous smaller studies which have demonstrated a higher rate of depression in adolescents with CFS/ME than in healthy controls9 10 and higher depression scores in those with CFS/ME than in the general population 12. We found that children with higher HADS depression scores also had higher HADS anxiety scores, which is consistent with previous studies 8 24.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study is consistent with previous smaller studies which have demonstrated a higher rate of depression in adolescents with CFS/ME than in healthy controls9 10 and higher depression scores in those with CFS/ME than in the general population 12. We found that children with higher HADS depression scores also had higher HADS anxiety scores, which is consistent with previous studies 8 24.…”
Section: Discussionsupporting
confidence: 93%
“…Several small case-control studies describe a higher rate of depression in adolescents with CFS/ME than in healthy controls9–11 and higher depression scores than seen in the general population 12. Rates of depression are higher in adolescents with CFS/ME than in adolescents with other chronic illnesses such as juvenile idiopathic arthritis and migraine 10 13.…”
Section: Introductionmentioning
confidence: 99%
“…However, drawing firm conclusions from this literature is difficult, as some studies have been quite small (table 1). The studies were set within tertiary referral centres and one was based within a psychology department,17 so the patient group may not be representative of children and adolescents in the general population. Comparison was made with normative population data,11 12 age- and sex-matched healthy controls from a local school,14 young people registered with a local general practitioner9 and with children referred to tertiary services with migraine14 and JIA 13.…”
Section: The Association Between Anxiety and Depression And Cfs/mementioning
confidence: 99%
“…12 The pathogenesis of the illness has not been completely delineated, 13 but it is most likely that CFS is characterized by a combination of both physiologic and psychologic impairments. 14 There is a growing international consensus that the CFS population should be subclassified because more homogeneous subgroups are less likely to reveal conflicting data among investigators. 15 Chronic fatigue syndrome with musculoskeletal system disorders such as widespread muscle and joint pain has been suggested as an important subclass of CFS.…”
mentioning
confidence: 99%